PENGARUH LAYANAN INFORMASI MENGGUNAKAN MEDIA POWTOON DALAM MENINGKATKAN PILIHAN KARIER PADA SISWA KELAS IX MTSN 1 BENGKULU UTARA - Anisa Nurjanah; Yessy Elita; Rita Sinthia (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aimed to describe the effect of information services using Powtoon media to improve understanding the direction of career choice for IX students of MTs Negeri 1 North Bengkulu. This research method uses an experimental method with one group pretest posttest design. The population in this study were IX students of MTs Negeri 1 North Bengkulu, totaling 148 students. The research sample is the students of class IX A study group totaling 15 students who have a low level of understanding the direction of career choice . Sampling used is purposive sampling. The data collection technique used a questionnaire with a Likert scale. The research data analysis technique used the (paired sample t-test). The results obtained in the study showed an increase in students' understanding the direction of career choice after being provided with information services using the Powtoon media. This can be seen from the results of hypothesis testing with t-test results of -21,965. This means that there is a significant effect on students' understanding the direction of career choice before and after the provision of information services using Powtoon media for class IX students of MTS Negeri 1 North Bengkulu.Keywords:Understanding the Direction of Career Choice, Media Powtoon, InformationService.